Establishment of a flow cytometric assay in the setting of renal transplant for T and B cell crossmatching - Ramparsad, Narisha (My University, 2014)
Donor specific crossmatching is performed prior to renal transplantation in order to determine the presence of pre-existing antibodies against donor HLA antigens which can result in hyperacute rejection. Flow cytometric crossmatching is reported in the literature to be a more sensitive and objective method of testing than the complement dependent cytotoxicity (CDC) method that is currently used in the Gauteng Province. A prospective analysis of the flow cytomeric crossmatch (FCXM) assay using the Luminex technology as the reference method was conducted. Forty-three samples were analysed. The T cell crossmatch (using a cutoff value of 2) revealed a sensitivity of 66.7%, a specificity of 83.8%, a positive predictive value (PPV) of 40% and negative predictive value (NPV) of 93.9%. The B cell crossmatch (using a cutoff value of 5) gave a sensitivity of 100%, specificity of 92.7%, and a PPV and NPV of 40 and100%, respectively. In addition, a retrospective analysis of clinical data for all patients transplanted during the period January 2008 to May 2009 was performed. Of a total of 50 patients assessed post transplant, none of the patients showed signs of hyperacute rejection, while twelve percent (12%) of patients revealed signs and symptoms suggestive of acute rejection. The validation of the flow cytometric crossmatch analysis was complex as there is no gold standard reference method. The assay was validated based on the clinical relevance of its high negative predictive value and the absence of hyperacute rejections in the clinical follow up. The rate of acute rejection found in this study is similar to that reported in literature.
A research report to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master Medicine in branch of Haematology
Keywords: Kidney Transplantation; Flow Cytometry